Rabindra Songs: The Humming of a Native Foreigner - izam Uddin , M. Abu Saleh N (Journal of Research in Humanities, 2023)
The worth-mentioning elements with which the conscience or spirit of the mass people of colonial Bengal during the time of great poet Rabindranath Thakur (1861-1941) was constructed were usually their native language, culture, love, thoughts, freedom movement, nature, farmers and misery in natural calamities. With this reality we can juxtapose Thakur’s songs or Rabindra Shangeet since it is expected that a literary figure will uphold the spirit of of his nation. Juxtaposed, we see that in his songs he not only refrains from upholding the spirit, but also tries to evade it. Thus epistemology delivered by Thakur’s songs is that Thakur, by writing the songs or any Bangaly listener, by worshipping them, is a foreigner despite being a native. This paper has the aim to explore how Thakur’s songs, evading mass people’s language, way of singing, nature of love, tradition of thoughts, the existance-related question of freedom from British colonizers, nature including its farmers and severe misery of the farmers during natural calamities, proves Thakur or any Bangaly worshipper of the songs to be a native foreigner as he hums them.